Dynamics and thermal stability of the bypass polymerase, DinB homolog (Dbh) - Soto, Jenaro; Moro, Sean L.; Cocco, Melanie J. (Frontiers in Molecular Biosciences, 2024)
The DinB homolog polymerase (Dbh) is a member of the Y-family of translesion DNA polymerases that can synthesize using a damaged DNA template. Since Dbh comes from the thermophilic archaeon Sulfolobus acidocaldarius, it is capable of functioning over a wide range of temperatures. Existing Xray structures were determined at temperatures where the protein is least active. Here we use NMR and circular dichroism to understand how the structure and dynamics of Dbh are affected by temperature (2-65 °C) and metal ion binding in solution. We measured hydrogen exchange protection factors, temperature coefficients, and chemical shift perturbations with and without magnesium and manganese. We report on regions of the protein that become more dynamic as the temperature is increased toward the functional temperature. Hydrogen exchange protection factors, and temperature coefficients reveal that both the thumb and finger domains are very dynamic relative to the palm and LF domains. These trends remain true at high temperature with dynamics increasing as temperatures increase from 35 °C to 50 °C. Notably, NMR spectra show that the Dbh tertiary structure cold denatures beginning at 25 °C and increases in denaturation as the temperature is lowered to 5 °C with little change observed by CD. Above 35 °C, chemical shift perturbation analysis in the presence and absence of magnesium and manganese reveals three ion binding sites, without DNA bound. In contrast, these bound metals are not apparent in any Dbh crystal structures of the protein without DNA. Two ion binding sites are confirmed to be near the active site, as reported in other Y-family polymerase, and we report a novel ion binding site in the LF domain. Thus, the solution-state structure of the Dbh polymerase is distinct from that of the solid-state structures and shows an unusually high cold denaturation temperature. 1 Introduction DinB homolog polymerase (Dbh) is produced by the thermophilic Archaea Sulfolobus acidocaldarius (S. acidocaldarius), that grows optimally at temperatures close to 75 -80 °C and pH values between 2-4 (Grogan, 1989